Clinical Outcomes in a Primary Care Practice Within a Center for Health Equity - Edward Demond Scott; Karen Gil; Billi Copeland King; Elizabeth Piatt (SAGE Publishing, 2015)
Objective: A Center for Health Equity that included a primary care practice was built in a neighborhood affected by long-term disparities related to race and class in order to promote health equity within the population. Changes in blood pressure and HbA1c (glycated hemoglobin) over 2 years were examined to assess the impact of providing culturally appropriate and patient-centered care. Methods: Data from June 1, 2012, to June 30, 2014 were obtained. Patients with high blood pressure or elevated HbA1c levels were treated according to evidence based guidelines. Blood pressure and HbA1c values at the first and last visit were compared using paired t tests. Results: Of the 390 patients seen with a systolic pressure ≥140 mm Hg, 358 came back for at least 1 visit (92%). By the time of the last visit, 70% had values <140 mm Hg. Mean decreases for systolic and diastolic pressure between the first and last visit were statistically significant (both P < .001). Of the 88 patients seen with HbA1c values ≥7%, 68 came back for at least 1 visit (77%). By the last visit, 31% had values <7%. The change in mean HbA1c levels between the first and last visits was statistically significant ( P = .001). Conclusion: Data from this report demonstrate statistically significant improved clinical outcomes among members of this community who sought and received care from physicians within this Center for Health Equity.